2022
DOI: 10.1039/d2tb01363k
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanocrystalline-doped folic acid-based super carbon dots for an enhanced antitumor effect in response to tumor microenvironment stimuli

Abstract: Copper nanocrystalline-doped folic acid-based super carbon dots (FA-CDs@Cux) were prepared to realize an enhanced antitumor effect in response to tumor microenvironment stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Figure 3c shows that CuPPaCC's • OH production capacity was time-dependent. The Fenton-like reaction decomposes H 2 O 2 to produce O 2 and • OH, 20,21 and Cu 2+ is an important Fenton-like reaction agent. 48 We have proved that CuPPaCC has a good Fenton-like reaction ability by using MB trapping • OH experiment, which indirectly proved that CuPPaCC has a good oxygen production ability.…”
Section: Ability To Producementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3c shows that CuPPaCC's • OH production capacity was time-dependent. The Fenton-like reaction decomposes H 2 O 2 to produce O 2 and • OH, 20,21 and Cu 2+ is an important Fenton-like reaction agent. 48 We have proved that CuPPaCC has a good Fenton-like reaction ability by using MB trapping • OH experiment, which indirectly proved that CuPPaCC has a good oxygen production ability.…”
Section: Ability To Producementioning
confidence: 99%
“…In the tumor microenvironment (TME), Fenton or Fenton-like reactions generate highly cytotoxic ROS (hydroxyl radical • OH). ,, However, the clinical application of PDT and CDT is limited by the hypoxia of the TME and the insufficient activity of H 2 O 2 . In addition, high concentrations of glutathione (GSH) deplete ROS, thereby reducing the efficacy of PDT and CDT. Reports have shown that combined PDT/CDT provides excellent therapeutic effects. The Fenton-like reaction decomposes H 2 O 2 to generate oxygen, which can relieve the hypoxia in the TME and provide a substrate for PDT, which in turn provides a substrate for CDT, and the thermal effect of light promotes the Fenton reaction . PDT/CDT has become a promising treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CDT is expected to synergistically enhance PDT. 19,20 Photothermal therapy (PTT), which is based on local high temperature damage to tumor cells after irradiation, has attracted much attention in cancer treatment. 21,22 The photothermal effects can be amplified during the PDT and CDT, 23,24 because ROS produced by PDT and CDT inhibit the expression of heat shock proteins, thereby increasing cell heat sensitivity and enhancing the PTT effect.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 CU(II) is a well-studied GSH consumption agent, which can deplete GSH (DG) overexpressed in TME through oxidation−reduction, and CU(I) could produce highly toxic •OH through the Fenton-like reaction with H 2 O 2 in TME. 12,13 In addition, it is reported that the metastasis, growth, and immunosuppression of cancer are closely related to the high expression of hypoxia-inducible factor-1α (HIF-1α). 19 However, Cu can also effectively improve the hypoxic environment of tumor cells by generating O 2 through Fentonlike reactions, thereby inhibiting the expression of HIF-1α.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of zero-dimensional nanomaterials, carbon dots (CDs) have recently made significant progress in cancer treatment due to high stability (the graphitized conjugated sp2 covalent carbon core) and good modifiability (rich functional groups on the surface). , Moreover, almost all carbon-containing substances can be used as precursors to prepare CDs, and some inherent characteristics of precursors could be retained. …”
Section: Introductionmentioning
confidence: 99%